Aspects of linguistic politeness in Serbian: a data-based comparison with German - Schlund, Katrin (Linguistik online, 2014)
The article investigates forms of address and request behaviour in Serbian as compared to German. It is based on an empirical study with authentic speech data and a survey among na-tive speakers of the two languages. While the corpora of authentic speech data document mainly service encounters and other minimal everyday interactions, the survey aims at reveal-ing the judgements and attitudes of native speakers towards different request strategies. The results point towards the well-known distinction between "solidarity cultures" in the East and "distance cultures" in the West. However, such findings must be treated with caution as other factors seem to influence the range of strategies available in the two languages as well.
Online veröffentlicht: 26. September 2014
Gesehen am 15.10.2025